Survey of Plant-Parasitic Nematodes Associated with Cotton in Nuh and Palwal Districts of Haryana - Vinod Kumar; Prakash Banakar; Anil Kumar; Priyanka Duggal (International Journal of Economic Plants, 2020)
An extensive survey was conducted to assess the frequency and abundance of plant-parasitic nematodes associated with cotton (Gossypium hirsutum L.) in Haryana (Nuh and Palwal districts) during 2018-20. Based on incidence, population density and associated damage on affected crops, root-knot nematode (Meloidogyne incognita) was considered to be the most important parasite of the crops under local condition. During 2018-19, a total of 11 soil and root samples of cotton were collected from Nuh and Palwal districts. Out of these, eight were found infected with M. incognita with 72.0% frequency of occurrence. The results revealed that out of 7 samples (Nuh), five were found infested with M. incognita with 71.4% frequency of occurrence. In Palwal district, this nematode had 75.0% frequency of occurrence with density range of 60-300 j2 200-1 cc soil. During 2019-20, a total of 27 soil and root samples of cotton were collected from Nuh and Palwal districts. Out of these, 14 were found infected with M. incognita with 51.8% frequency of occurrence. The results revealed that out of 21 samples (Nuh), 12 were found infested with M. incognita with 57.1% frequency of occurrence and density range of 95-690 j2 200-1 cc soil. In Palwal district, this nematode had 33.3% frequency of occurrence (2 out of 6 samples) with density range of 135-435 j2 200-1 cc soil. Other plant parasitic nematodes which were found associated with the cotton belonged to Rotylenchulus reniformis, Hoplolaimus sp., Helicotylenchus sp. and Tylenchorhynchus sp.